Portable property : Victorian culture on the move - Plotz, John, 1967- (Princeton University Press, 2008)
What fueled the Victorian passion for hair-jewelry and memorial rings? When would an everyday object metamorphose from commodity to precious relic? In Portable Property, John Plotz examines the new role played by portable objects in persuading Victorian Britons that they could travel abroad with religious sentiments, family ties, and national identity intact. In an empire defined as much by the circulation of capital as by force of arms, the challenge of preserving Englishness while living overseas became a central Victorian preoccupation, creating a pressing need for objects that could readil.